RELIGIOUS IMAGE IN MADHAVA KANDALI’S RAMAYANA AND BHANUBHAKTA’S RAMAYANA - Gogoi, Bhupen (International Journal of Psychosocial Rehabilitation, 2020)
Ramayana is one of the great epic among the two Indian epics. It is composed by Valmiki in Sanskrit. Ramayana is embedded in every stage of the life of Indian society. Also, Ramayana is embedded in social rituals, folk-traditions, religion, dances, music and literature of the people of different caste-tribes of India. The popularity of Ramayana by Valmiki has increased so much that it has been translated into all the regional languages of India. Now it is also being translated into various languages of the world. Madhava Kandali of Assam has translated the verses of the Valmiki’s Ramayana to Assamese language in 4th century A.D. In the entire North-East India, Kandali’s Ramayana was the earliest Ramayana that was composed in the rigional language. In between 1840 to 1853, Nepali poet Bhanubhakta Acharya of Nepal has composed the Nepali Ramayana. It is the translation of Sanskrit ‘Adhyatma Ramayana’. Despite the disruption of five century, thre is much similarities and dissimilarities between the both Ramayana.